2017
DOI: 10.17323/2411-7390-2017-3-3-39-49
|View full text |Cite
|
Sign up to set email alerts
|

Enquiry-Based Approach in Mobile-Supported Classroom to Develop Language Skills

Abstract: This article investigates the pedagogical impact of both the mobile-testing system PeLe and an enquiry-based approach to language skills development in the context of mobileassisted language learning. The study aims to work out a methodological framework for PeLe implementation into a language classroom through immediate feedback and formative assessment. The framework was developed and pilot tested in a joint research project, MobiLL, by EFL teachers at Lomonosov Moscow State University (Russia) and Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Hence, the students who participated in mastery learning instruction participated in peer feedback, corrective procedures, and formative assessment, and these helped them enhance their writing skills results. Here, researchers such as Gamlem and Smith (2013) and Titova and Samoylenko (2017) reported that feedback and formative assessment are essential for learning and teaching. Students develop the positive perception that they can do better when they get support from their classmates and they engage actively with the designed objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the students who participated in mastery learning instruction participated in peer feedback, corrective procedures, and formative assessment, and these helped them enhance their writing skills results. Here, researchers such as Gamlem and Smith (2013) and Titova and Samoylenko (2017) reported that feedback and formative assessment are essential for learning and teaching. Students develop the positive perception that they can do better when they get support from their classmates and they engage actively with the designed objectives.…”
Section: Discussionmentioning
confidence: 99%